Students' Characters of Learning at State Senior High School 1 Purworejo - Arkimawati, Ida Festiani; , Prof. Dr. Bambang Sumardjoko, M.Pd; , Drs. Sigit Haryanto, M.Hum (2013)
This research aims at acknowledging (1) Students' characters of learning at State Senior High School 1 Purworejo (2) Students' characters of learning in non-academic discipline at State Senior High School 1 Purworejo, dan (3) Students' excellence characters of learning at State Senior High School 1 Purworejo in academic discipline or non-academic discipline as well. The research is a qualitative inqury that conducted at State Senior High School 1 Purworejo. Primary subjects of the research were a headmaster, teachers and students. The research utilised proficiency of data collection i.e. in-depth interviews, observations and documentations. Meanwhile proficiency of data analysis in this research utilised analysis model i.e. data collection, data reduction, data presentation and concise. In the meantime validity of this research used data trianguality. The study showed (1) Learning at State Senior High School 1 Purworejo refered to development of the Education Unit Level Curriculum (KTSP). Teaching and learning process used two languanges (bilingual). The learning was conducted using multimedia basis. Learning method was inovative utilising e-learning basis and moving class learning model leaded to grow actively student's character of learning in academic discipline and encouraged students to participate in learning activities enthusiastically. (2) Implementation of extracurricular activities was commenced by program establishment and budget plan as well as prestige basis. Meanwhile a guide teacher of extracurricular activities must be a professional one in its field. A teacher role is as a consultant, motivator and faslitator. Karawitan (a type of music) changed to become intracurricular subject as a proof of cultural love. Thus the accomplishments encouraged the student to achieve masteries in regional level and national level as well. A competition participant would get particular counselling of lessons from teachers outside of learning and teaching process. Developing extracurricular activities at State Senior High School 1 Purworejo was in appropriate with interests and talents of students and led them to achieve maximumly. (3) Conducting teachers' characters as professional teachers who always applied their characters based on RPP and teachers' role plays. OSIS work programes using vision of "the love gains the future" were implementation of character development consisted of 18 character values as developed character reflection of curiculum centre, development and cultural education & nation character: School guidance, 2009: 9-10. Proving State Senior High School 1 Purworejo as an excellent character school in its academic and non-academic fields